Modification of Risk Assessment Value to Test Industry Reliability - Sorooshian, Shahryar (2015)
This paper is in a form of a technical note, in which modified method of industry reliability analysis is reviewed. This paper introduces a multi-expert approach group decision making analysis for Risk Assessment Value (RAV), which directly tests the reliability of the system (industry). A case of construction industry has been studied for verification of the method. Reviewed RAV modified technique helps to assess the value of industry reliability; and brings contribution to the body of risk management knowledge.